Development of epitaxial AlxSc1−xN for artificially structured metal/semiconductor superlattice metamaterials. Issue 2 (18th September 2014) - Saha, Bivas; Saber, Sammy; Naik, Gururaj V.; Boltasseva, Alexandra; Stach, Eric A.; Kvam, Eric P.; Sands, Timothy D.
<x xml:space="preserve">Abstract</x> Development of epitaxial, monocrystalline metal/semiconductor superlattices with well‐defined, sharp and abrupt interfaces has been long sought to design the next generations of electronic, optic and thermal transport based devices. With a motivation to integrate nitride semiconductors with rocksalt transition nitride metals (such as TiN, TaN, ZrN etc.), Saha et al. have developed rocksalt AlxSc1‐xN semiconductors with tunable structural, electronic, and optical properties that enable high quality epitaxial rocksalt metal/AlxSc1‐xN superlattices with a wide range of accessible metamaterials properties. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>